Diffusion‐time dependence of diffusional kurtosis in the mouse brain - Aggarwal, Manisha; Smith, Matthew D.; Calabresi, Peter A. (Magnetic resonance in medicine, 2020)
Purpose To investigate diffusion‐time dependency of diffusional kurtosis in the mouse brain using pulsed‐gradient spin‐echo (PGSE) and oscillating‐gradient spin‐echo (OGSE) sequences. Methods 3D PGSE and OGSE kurtosis tensor data were acquired from ex vivo brains of adult, cuprizone‐treated, and age‐matched control mice with diffusion‐time (tD) ~ 20 ms and frequency (f) = 70 Hz, respectively. Further, 2D acquisitions were performed at multiple times/frequencies ranging from f = 140 Hz to tD = 30 ms with b‐values up to 4000 s/mm2. Monte Carlo simulations were used to investigate the coupled effects of varying restriction size and permeability on time/frequency‐dependence of kurtosis with both diffusion‐encoding schemes. Simulations and experiments were further performed to investigate the effect of varying number of cycles in OGSE waveforms. Results Kurtosis and diffusivity maps exhibited significant region‐specific changes with diffusion time/frequency across both gray and white matter areas. PGSE‐ and OGSE‐based kurtosis maps showed reversed contrast between gray matter regions in the cerebellar and cerebral cortex. Localized time/frequency‐dependent changes in kurtosis tensor metrics were found in the splenium of the corpus callosum in cuprizone‐treated mouse brains, corresponding to regional demyelination seen with histological assessment. Monte Carlo simulations showed that kurtosis estimates with pulsed‐ and oscillating‐gradient waveforms differ in their sensitivity to exchange. Both simulations and experiments showed dependence of kurtosis on number of cycles in OGSE waveforms for non‐zero permeability. Conclusion The results show significant time/frequency‐dependency of diffusional kurtosis in the mouse brain, which can provide sensitivity to probe intrinsic cellular heterogeneity and pathological alterations in gray and white matter.